Numerical Solution of Fuzzy Delay Functional Differential Equations by Euler Method - Prakash, P.; Senthilvelavan, S. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study the numerical solution of fuzzy delay functional differential equations by using Euler method. Examples are presented to illustrate the computational aspects of the above method.